(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Two different noninvasive ambulatory hemodynamic monitoring devices (belt-type and chest-type) based on Electrocardiogram (ECG) and Impedance Cardiography (ICG) has been designed, fabricated and tested. Hardware designs of the two ambulatory hemodynamic monitoring devices based on Tetrapolar configuration and placement of the electrodes were introduced. Hemodynamic parameters such as Stroke Volume (SV), Cardiac Output (CO) and Cardiac Index (CI) can be estimated according to Kubicek Formula by extracting characteristic points and characteristic periods in the ICG Signal. CI is CO divided by body surface area. CI is comparable among different people because it is not influenced by the body height and weight. The body's physiological responses to postural change are primarily a reaction to the change of gravity, because change of gravity can cause changes of blood flow distribution in organs and tissues. Different body postures (upright or supine) can result in reducing or rising of CO. The detection accuracy has also been validated with a commercial ICG detection instrument from Mindray company, and the correlation coefficient is 0.83.